Estratégias comunicativas para dar visibilidade à dança: o papel da mídia, as políticas públicas, a criação de um campo de conhecimento - Gonçalves, Marilia Gabriela (2008)
The creation of a public for contemporary art has been a recurring theme in different forums of debate in Brazil as well as abroad. This has led to discussions related to cultural journalism, to changes in the criteria of curatorship and the production of culture, as well as to the study of new bibliographies to evaluate art, culture and power. The hypothesis of this dissertation for a Master s Degree is that, in this context, there is a fundamental problem of communication. This does not apply exclusively to the relationship between the artist and the public, but involves a complex system of power and the means of transmitting information. To study it and propose strategies for dealing with some of the main difficulties which have been barriers to the development of broad projects, it is necessary to discuss the role of the media, some laws during the last decade to encourage culture, and the action of some public and private institutions in this context. As a case study, we selected dance in Brazil, drawing a diagnosis of the problems of communication that have overrun this field of knowledge since the arrival of ballet in the country, in 1927, and which have continued doing so until today. This is because there are standards that are fixtures. The scenario of theoretical research includes reflections on the bodymedia theory of Christine Greiner e Helena Katz, the studies on translation of Boaventura de Sousa Santos (important to understanding how dance was presented to the public as a mechanism of power), the concept of mimesis developed by Homi Bhabha, the concept of inclusion as a means of exclusion studied by Giorgio Agamben and the discussions on the term Cultural Journalism as raised by Daniel Piza and as yet to be answered for the institutions that work on questions related to cultural media. Through this work, we hope to detect the sounds of communication that exist in this system which aims at forming a public, by showing the path of the relationship between the public, the artist and the accompanying processes (media, politics, power) and, insofar as this is possible, suggesting new strategies to achieve this